The later Saxon and early Norman manorial settlement at Guiting Power : archaeological investigation of a domesday book entry - Marshall, Alistair (Alistair J.) (Archaeopress, 2020)
This volume outlines an investigation of the early manor at Guiting Power, a village in the Cotswolds with Saxon origins, lying in an area with interesting entries in the Domesday Survey of 1086.